Effects of Group Pregnancy Care Combined with Nutritional Guidance on Patients with Gestational Diabetes Mellitus: A Prospective Study - Xiaocheng He; Meijing Zhao; Huiyan Wang; Yaping Xie; Huifen Zhao (Clinical and Experimental Obstetrics & Gynecology)
Background: The rising incidence of gestational diabetes mellitus (GDM), driven by modern lifestyle and dietary changes, underscores the need for effective management strategies. This prospective observational study evaluates the effectiveness of group prenatal care combined with nutritional guidance in managing GDM. Methods: This research is a prospective study. Convenience sampling was used to identify pregnant women who registered for and received regular prenatal care at the Second Affiliated Hospital of Fujian Medical University obstetrics and gynecology department from February 2023 to February 2024. Based on the recorded antenatal care methods, the study included 50 patients in the observation group and 46 patients in the control group. The control group received routine prenatal care, whereas the observation group received group prenatal care supplemented with nutritional guidance. Dietary compliance, GDM knowledge, self-management ability, and perceived social support were assessed and compared between the two groups. Results: Post-intervention analysis revealed that the observation group exhibited significantly higher scores in dietary compliance, GDM knowledge, self-management ability, and perceived social support compared to the control group (p < 0.05). Conclusions: The implementation of group prenatal care combined with nutritional guidance significantly improves dietary compliance, enhances GDM knowledge, and boosts self-management skills and perceptions of social support in pregnant women with GDM. Clinical Trial Registration: The study is registered on https://www.isrctn.com/ (registration number: ISRCTN14579442).